An ‘Amalgamated-Model' of performance measurement for private finance initiative project in Malaysia / Nor Suzila Lop, Kharizam Ismail and Haryati Mohd Isa - Nor Suzila, Lop; Kharizam, Ismail; Haryati, Mohd Isa (Universiti Teknologi MARA, Perak, 2017)
In Private Finance Initiative (PFI), payment for services is based on pre-determined standards andperformance. Thus, Key Performance Indicators (KPIs) have been used to measure this performance. However, in Malaysia, the absence of an effective KPIs is identified as one of the core criticisms for measuring the PFI projects performance. Therefore, two objectives are established which are; to investigate the implementation of various PFI performance measurement models across the globe and how these models can be adopted within PFI in the Malaysia’s context. Finally, an ‘Amalgamated-Model’ of Performance Measurement approach for PFI Project in Malaysia is proposedfor measuring the project performance. The outcomes of this research can serve as a theoretical base for the improving performance measurement model in monitoring and measuring PPP projects performance in Malaysia.